MEMBANGUN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA USAHA RITEL PASAR TRADISIONAL DI KOTA TANGERANG SELATAN - Thio Lie Sha; M Tony Nawawi Tony Nawawi; Rosmita Rasyid Rosmita Rasyid (Jurnal Bakti Masyarakat Indonesia, 2021)
In community service activities that have been carried out in Tangerang City, the aim of this activity is to conduct training in retail businesses in South Tangerang, in building relationships with customers. Providing knowledge on how to build good relationships with customers is expected to increase customer loyalty. This activity refers to the results of internal grant research from PKM team members on customer relationship management (CRM). For retail businesses, it is very important to build customer relationship management (CRM) in increasing and maintaining loyal customers. The partner that is used as a place of activity is engaged in retail trading in eight traditional markets in South Tangerang, and has been in business for 6 years. With preliminary observations made on partners, several problems faced by these partners were identified, including a). Lack of knowledge of partners in doing good relationships with customers. b) lack of knowledge of partners to analyze customer relationship management (CRM) programs in maintaining customers. Based on the analysis of partner problems, there is still weak knowledge of customer relationship management (CRM) so that partners have not been able to build relationships with customers. The method offered in this activity is training online retail business owners. The results of this activity indicate that the partners are very enthusiastic in listening to and discussing the CRM material delivered by the PKM TEAM. Thus the understanding of partners about CRM will be further improved. ABSTRAK:Pada kegiatan pengabdian kepada masyarakat yang telah dilaksanakan di Kota Tangerang, yang bertujuan untuk kegiatan ini adalah melakukan pelatihan pada usaha ritel di Tangerang Selatan, dalam membangun hubungan dengan pelanggan. Dengan pembekalan pengetahuan tentang cara membangun hubungan yang baik dengan pelanggan diharapkan dapat meningkatkan loyalitas pelanggan. Kegiatan ini mengacu dari hasil penelitian hibah internal dari anggota tim PKM tentang customer relationship managemen (CRM). Bagi usaha ritel sangat penting membangun customer relationship managemen ( CRM) dalam meningkatkan dan mempertahankan pelanggan yang setia. Mitra yang dijadikan tempat kegiatan adalah bergerak dalam bidang perdagangan eceran di pasar tradisional delapan Tangerang Selatan , dan sudah melakukan usaha selama 6 tahun. Dengan observasi awal yang dilakukan pada mitra teridentifikasi beberapa persoalan yang dihadapi mitra tersebut diantaranya a). Kurangnya pengetahuan mitra dalam melakukan hubungan yang baik dengan pelanggan. b) kurangnya pengetahuan mitra menganalisis program customer relationship managemen (CRM) dalam mempertahankan pelanggan. Berdasarkan analisis masalah mitra , masih lemahnya pengetahuan akan customer relationship managemen (CRM) sehingga mitra belum mampu membangun hubungan dengan pelanggan. Metode yang ditawarkan pada kegiatan ini adalah pelatihan kepada pemilik usaha ritel secara daring. Hasil kegiatan ini menunjukkan bahwa mitra sangat antusias dalam mendengarkan dan berdiskusi tentang materi CRM yang disampaikan oleh TIM PKM. Dengan demikian pemahaman mitra tentang CRM akan lebih meningkat.